Should All Massively Transfused Patients Be Treated Equally? An Analysis of Massive Transfusion Ratios in the Nontrauma Setting. Issue 8 (August 2017) - Etchill, Eric W.; Myers, Sara P.; McDaniel, Lauren M.; Rosengart, Matthew R.; Raval, Jay S.; Triulzi, Darrell J.; Peitzman, Andrew. B.; Sperry, Jason L.; Neal, Matthew D.
Abstract : Objectives: Although balanced resuscitation has become integrated into massive transfusion practice, there is a paucity of evidence supporting the delivery of high ratios of plasma and platelet to RBCs in the nontrauma setting. This study investigated the administration of blood component ratios in the massively transfused nontrauma demographic. Design: Retrospective analysis of a prospective, observational cohort of massively bleeding patients. Setting: Surgical and critically ill patients at a tertiary medical center between 2011 and 2015. Patients: Massively transfused nontrauma patients. Interventions: Patients receiving plasma, platelet, and RBC transfusions were categorized into high and low ratio groups and analyzed for differences in characteristics and clinical outcomes. Measurements and Main Results: The primary outcome was 30-day mortality. Secondary outcomes included 48-hour mortality, hospital length of stay, ICU length of stay, and ventilator-free days. Among 601 massively transfused nontrauma patients, cardiothoracic surgery and gastrointestinal or hepato-pancreatico-biliary bleeds were the most common indications for massive transfusion. Higher fresh frozen plasma ratios (> 1:2) were not associated with increased 30-day mortality. A high platelets-to-packed RBCs ratio (> 1:2) was associated with decreased 48-hour mortality (10.5% vs 19.3%; p = 0.032), but not 30-day mortality. Fresh frozen plasma-to-packed RBCs and platelets-to-packed RBCs ratios were not associated with 30-day mortality hazard ratios after controlling for baseline characteristics and disease severity. Conclusions: The benefits of higher ratios of fresh frozen plasma-to-packed RBCs and platelets-to-packed RBCs described in trials of trauma patients were not observed in this analysis of a nontrauma, massively transfused population. These data suggest that greater than 1:2 ratio transfusion in the setting of massive hemorrhage may not be appropriate for all patients, and that further research to guide appropriate resuscitation strategies in nontrauma patients is warranted. Abstract : Supplemental Digital Content is available in the text.